PROJECT-BASED LEARNING TO RAISE STUDENTS’ SPEAKING ABILITY: ITS’ EFFECT AND IMPLEMENTATION (A MIX METHOD RESEARCH IN SPEAKING II SUBJECT AT STAIN PONOROGO) - Rohmahwati, Pryla (IAIN PONOROGO, 2015)
This research tries to attempt to know the effect of Project-based learning toward speaking ability and its? effective implementation. The design of the research sequential was designs in which data that are collected and examined in one stage inform the data collected in the next phase. This research applied a quantitative design for the first stage. It is categorized into causal comparative method, or ex post facto research design and the second stage is qualitative design. Population in this research was the 2 STAIN Ponorogo. The total numbers of the students are 85 students and the sample was 70 students. The researcher used questionnaires, test, observation and interview as data collection. Since the hypothesis is intended to find the effect of the Project-Based Learning toward students? speaking ability, the Simple Linier Regression by using SPSS 19.00 for Windows was applied. The second phase, the result of observation and interview were analyzed by Miles and Huberman?s view of qualitative data analysis consisting of data reduction, data display, and drawing conclusion. The result of analysis showed that there was significant effect of Project-Based Learning toward students? speaking ability. Moreover, the effective procedures for the implementation of Project-Based Learning are (a) dividing the class into group, (b) explaining the project and (c) performing the project. At last, the students showed significantly positive attitude toward the implementation of Project-Based Learning in speaking class. semester of English Department Students in STAIN Ponorogo. The total numbers of the students are 85 students and the sample was 70 students. The researcher used questionnaires, test, observation and interview as data collection. Since the hypothesis is intended to find the effect of the Project-Based Learning toward students? speaking ability, the Simple Linier Regression by using SPSS 19.00 for Windows was applied. The second phase, the result of observation and interview were analyzed by Miles and Huberman?s view of qualitative data analysis consisting of data reduction, data display, and drawing conclusion. The result of analysis showed that there was significant effect of Project-Based Learning toward students? speaking ability. Moreover, the effective procedures for the implementation of Project-Based Learning are (a) dividing the class into group, (b) explaining the project and (c) performing the project. At last, the students showed significantly positive attitude toward the implementation of Project-Based Learning in speaking class.